2010
DOI: 10.1055/s-0030-1255032
|View full text |Cite
|
Sign up to set email alerts
|

Body Composition After Endogenous (Cushing's Syndrome) and Exogenous (Rheumatoid Arthritis) Exposure to Glucocorticoids

Abstract: • ▶ body composition • ▶ Cushing ' s syndrome • ▶ rheumatoid arthritis • ▶ glucocorticoids Body Composition After Endogenous (Cushing ' s Syndrome) and Exogenous (Rheumatoid Arthritis) Exposure to Glucocorticoids abolition of the normal male to female diff erence in visceral fat [5]. It has been assumed that resolution of hypercortisolism is followed by normalization of body composition; a decrease in fat mass has been reported in the early recovery after successful treatment of CS [6, 7]. However, patients wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 19 publications
1
25
0
Order By: Relevance
“…total body fat and trunk fat is higher in endogenous than exogenous CS (107). Recently, it has been shown that patients with CS due to primary pigmented nodular adrenal disease have a typically milder obese phenotype than other forms of CS, even when their cortisol levels are comparable and their CS is not atypical or cyclical (108).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…total body fat and trunk fat is higher in endogenous than exogenous CS (107). Recently, it has been shown that patients with CS due to primary pigmented nodular adrenal disease have a typically milder obese phenotype than other forms of CS, even when their cortisol levels are comparable and their CS is not atypical or cyclical (108).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…Excess exposure to cortisol results in the development of insulin resistance, visceral fat formation, and reduction in lean body mass, and predisposes individuals to diabetes mellitus, premature coronary artery disease, and osteoporosis (Faggiano et al 2003; Kelly et al 1998; Pearce et al 1998; Resmini et al 2010; Tauchmanova et al 2002). Excess cortisol exposure also disrupts cognition and mood as well as other neural processes by inducing dendritic remodeling, suppressing neurogenesis, and causing atrophy of the hippocampus (Sapolsky et al 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Oral glucose tolerance test, 24-hour ambulatory blood pressure monitoring, echocardiography, electrocardiogram, and carotid ultrasound have been proposed in the followup to establish the cardiovascular risk in cured CS [31,141]. A combination of treatments directed both against hypercortisolism and aimed at controlling cardiovascular risk factors seems appropriate to reduce cardiovascular events in these patients [1,2,59].…”
Section: Discussionmentioning
confidence: 99%